2015
DOI: 10.17221/8175-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Use of natural substances for boar semen decontamination

Abstract: ABSTRACT:The aim of this study was to investigate the antibacterial activity and toxicity for sperm cells of the natural substances gallic acid, methyl gallate, ethyl gallate, propyl gallate, octyl gallate, thymol, carvacrol and eugenol. The antibacterial activity of these natural substances and selected combinations of them against bacterial strains isolated from boar ejaculates was determined using the microdilution and macrodilution method in Mueller-Hinton broth. The most effective natural substances again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 76 publications
(88 reference statements)
1
7
0
1
Order By: Relevance
“…These authors also observed that agents related to this family contaminated 40.68% of semen samples assessed, and these are related to reduced motility and increased sperm pathologies. Moreover, these microorganisms might be involved in inflammatory processes of the endometrium of inseminated sows (5,24). While sperm motility, sperm morphology, and concentration of the SD produced are the parameters commonly used to assess semen quality, the microbiological evaluation is not a routine practice in boar semen evaluation, and may indicate other potential indicators of poor semen quality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These authors also observed that agents related to this family contaminated 40.68% of semen samples assessed, and these are related to reduced motility and increased sperm pathologies. Moreover, these microorganisms might be involved in inflammatory processes of the endometrium of inseminated sows (5,24). While sperm motility, sperm morphology, and concentration of the SD produced are the parameters commonly used to assess semen quality, the microbiological evaluation is not a routine practice in boar semen evaluation, and may indicate other potential indicators of poor semen quality.…”
Section: Discussionmentioning
confidence: 99%
“…Estos autores también observaron que los agentes relacionados con esta familia contaminaron el 40,68% de las muestras de semen evaluadas, y éstos están relacionados con la reducción de la motilidad y el aumento de las patologías espermáticas. Además, estos microorganismos pueden estar implicados en procesos inflamatorios del endometrio de las cerdas inseminadas (5,24). Aunque la motilidad de los espermatozoides, su morfología y la concentración de la DS producida son los parámetros comúnmente utilizados para evaluar la calidad del semen, la evaluación microbiológica no es una práctica rutinaria en la evaluación del semen porcino, y puede indicar otros posibles indicadores de mala calidad.…”
Section: Discussionunclassified
“…In this study, chitosan-phytochemical conjugates were synthesized by conjugating HAs with chitosan following the previous method [17,24]. It was then assessed for the antibacterial activity of chitosan-phytochemical conjugates against acne-related bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…Hydroxycinnamic acids (HAs) (having sinapic acid, caffeic acid, and ferulic acid) are naturally occurring phytochemicals from plants and have been used in pharmaceuticals, cosmetics, and the food industry [ 21 , 22 , 23 ]. In this study, chitosan-phytochemical conjugates were synthesized by conjugating HAs with chitosan following the previous method [ 17 , 24 ]. It was then assessed for the antibacterial activity of chitosan-phytochemical conjugates against acne-related bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…CFA and CSA showed the MIC values of 16 μg/mL to 256 μg/mL against acne-related bacteria. Interestingly, chitosan, and the chitosan-phytochemical conjugates showed very strong antibacterial activity against P. aeruginosa in the MICs range of 16 to 32 μg/mL, while Mazurova et al [21] reported that MICs of natural substances (gallic acid, methyl gallate, ethyl gallate, propyl gallate, octyl gallate, carvacrol, thymol, and eugenol) have range of 300 to 2,400 μg/mL. Generally, P. aeruginosa has high-level resistance to antibiotics and substances derived from natural materials due to the low permeability and the action of multidrug efflux pumps [5,22].…”
Section: Antibacterial Effect Of Chitosan-phytochemical Conjugates Agmentioning
confidence: 99%